An In-Depth Analysis of Choice of Law Rules in Consumer Contracts: A Focus on the African Continental Free Trade Area - Fiattor, Ethel (Journal of Law, Society and Development, 2023)
Choice of law is a perplexing concept due to the importance of party autonomy, the diversity of connecting factors, and the variety of different contractual issues. The problem of choosing a governing law is complicated in consumer contracts by industrialised mechanisms depriving consumers of negotiation rights. The core mandate of the African Continental Free Trade Area (AfCFTA) is to establish a single market for goods and services associated with the free movement of legal persons for economic integration. This objective requires a harmonised consumer protection policy to resolve the diverse consumer protection regimes applicable in state parties within AfCFTA member states. This policy should provide suitable consumer protection mechanisms generally and in the context of choice of law specifically. Implementing a draft competition policy bestows a legitimate mandate on the AfCFTA to negotiate a continental framework on consumer protection as both fields of law complement each other to safeguard consumer rights in cross-border trade. This article argues the dynamics of providing adequate choice of law rules on consumer contracts to inform suitable mechanisms on consumer interest within the AfCFTA. The article discusses the abuse of choice of law clauses in consumer contracts, affecting consumers’ rights in cross-border contracts within the AfCFTA. It suggests a harmonised consumer protection policy to regulate and mitigate these clauses. The article also examines trends in Global North jurisdictions like the European Union to inform a context-specific institutional framework for the AfCFTA’s choice of law rules.
Keywords: AfCFTA; Applicable law; Choice of law; Consumer protection; Economic integration; Harmonisation; International law; ZLECAf

Redesigning Protection for Consumer Autonomy: The case-study of dark patterns in European private law - Guerra, Giorgia (FrancoAngeli, 2023)
European legal protection of consumer autonomy has been significantly changed in the digital environment, where algorithm-driven systems perform everything. This book focuses on protecting consumer autonomy facing the pervasive and global phenomenon of dark patterns: the expression includes various tactics that manipulate consumers by altering online choice architecture to thwart user preferences for objectionable ends. Overloading, skipping, stirring, hindering, and flicking are examples. Moving from the perspective that the sole traditional information approach is ineffective in protecting autonomy, the adopted methodology considers the multiple concerns revolving around the tight combination of transparent information and fair digital architectural design. Consequently, the comparative study of the new suitable regulatory directions arises across different legal fields, including data protection, consumer, and competition law. The relationship between deceptive designs, the nature of human-digital architecture interaction, and the techno-legal paradigms emphasises which future changes in European private law could integrate legal rules into fair designs to protect digital consumer autonomy effectively. Specific importance will be attributed to the functionality of comparative methodology to include non-legal essential insights (e.g. behavioural, informatic elements) into pragmatic and global regulatory paths and models.
Keywords: Autonomy; Consumer law; Dark Patterns; Data protection law; Design regulation; Digital law; European private law